Boosting Patient Revisit Intention Through Tech-Driven Service Innovations and Brand Recognition - Fransisca Halim; Supriyantoro Supriyantoro; Johanes Johanes (Global Management: International Journal of Management Science and Entrepreneurship, 2026)
Increasing competition in the healthcare industry requires hospitals not only to attract new patients but also to maintain long-term relationships with existing patients by strengthening revisit intention. However, many healthcare institutions still face challenges in developing effective service strategies and technological innovations that can sustainably encourage patients to return for future healthcare services. This study aims to analyze the effects of service differentiation strategy and technology-based service innovation (TBSI) on patient revisit intention, with brand recognition serving as a mediating variable, at the outpatient clinic of Tzu Chi Hospital PIK. A quantitative research design was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships among variables. Data were collected through structured questionnaires distributed to outpatients who had previous experience receiving healthcare services at the hospital. The analysis involved validity and reliability testing, descriptive analysis using the three-box method, and structural model evaluation to test the proposed hypotheses. The findings indicate that service differentiation strategy and technology-based service innovation positively and significantly influence patient revisit intention. Furthermore, brand recognition demonstrates a positive and significant effect on revisit intention and mediates the relationships between service differentiation strategy, technology-based service innovation, and revisit intention. These findings suggest that differentiated healthcare services and technology-enabled innovations are more effective in increasing patient revisit intention when they strengthen patients’ recognition and perceptions of hospital brands. This study concludes that strengthening brand recognition through service differentiation and technological innovation is essential for improving patient loyalty and sustaining competitive advantage in healthcare services.